2000
DOI: 10.1103/physrevlett.85.389
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Absorption in a Quantum Dot

Abstract: The excitonic absorption spectrum of a single quantum dot is investigated theoretically and experimentally. The spectrum is determined by an interacting electron-valence-hole complex. We show that the mixing of quantum configurations by two-body interactions leads to distinct absorption spectra controlled by the number of confined electronic shells. The theoretical results are compared with results of photoluminescence excitation spectroscopy on a series of single self-assembled In0.60Ga0.40As quantum dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 25 publications
(10 reference statements)
1
81
0
Order By: Relevance
“…Neither of these corresponds to LO phonon energies of the materials in our sample. The interpretation of the observed PLE peaks is rather consistent with the interpretation of Hawrylak et al 7 who performed single-dot PLE on similar types of QDs and attributed observed resonances to interband transitions between p-and d-shell QD bound states.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Neither of these corresponds to LO phonon energies of the materials in our sample. The interpretation of the observed PLE peaks is rather consistent with the interpretation of Hawrylak et al 7 who performed single-dot PLE on similar types of QDs and attributed observed resonances to interband transitions between p-and d-shell QD bound states.…”
Section: Resultssupporting
confidence: 74%
“…However, it has been shown that the presence of excited states, through configuration mixing, will influence the energy shell structure of all bound states, including the ground state. 7 Simply put, maximizing the application potential of QD systems requires understanding and modeling their energy shell structure, including the excited states, as precisely as possible.…”
Section: Introductionmentioning
confidence: 99%
“…8 LO-phonon replicas have been resolved for single InAs/GaAs QDs in PL-excitation spectroscopy, but the coupling strength was not extracted, nor its association with charged excitonic states investigated. 10 For single CdSe/ZnCdSe QDs, data of first-and second-order LO-phonon replicas for both the exciton and the biexciton have been reported. 11 The polar coupling in such II-VI compounds is larger compared to III-V materials, and the HuangRhys parameter was determined to be 0.035 and 0.032 for the exciton and biexciton, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the pronounced and so far unavoidable growth-induced inhomogeneous broadening in ensembles of semiconductor QDs, the recent development of single QD spectroscopy has provided a wealth of new information (15). It is now understood that sufficiently confined QDs resemble in many respect atomic systems, showing atomic-like densities of states (16; 17; 18), a shell-like absorption spectrum (19) and -at low temperatures - (20; 21). In addition, the large extent of the electron wave function in QDs gives rise to excitonic dipole moments of 10 -100 Debye, much larger than those of atomic systems.…”
Section: Introductionmentioning
confidence: 99%